Value addition of low fat chicken sausage with rice and wheat flour - Rokib, M; Habib, M; Hashem, MA; Ali, MS (Bangladesh Journal of Animal Science, 2020)
The study was conducted to evaluate the effect of rice and wheat flours on low fat chicken sausages. Sausages were prepared into three different groups: control; broiler breast meat sausage without any flour (T1), sausage with addition of 10% rice flour (T2) &10% wheat flour (T3). All parameters were analyzed at 0, 15th and 30th days of storage period. The proximate compositions of different sausages were analyzed and highly significant (p<0.01) differences were found in DM (%) and CP (%). Significantly (p<0.01) lower DM (%) and higher CP (%) was found in T1. Both DM (%) and CP (%) content were increased with increase of storage time. The storage period have significant (p<0.01) effect on different biochemical (FFA, POV and TBARS value) and microbial (TVC, TCC and TYMC) test. In both cases the values were increased with increase of storage period. Different types of sausage and storage period have an effect on redness (a*) value. In sensory analysis, significantly lower flavor, juiciness and tenderness were found in T1. Although flavzAQAor, juiciness and tenderness were varied during sensory evaluation, overall acceptability did not differ among the three treatments. Results of this study revealed that low fat chicken sausages can be made with 10% rice and wheat flour without lowering the overall acceptability. Bang. J. Anim. Sci. 2019. 48 (2): 99-107